Total ionizing dose effects on resistance stability of Pt/HfO2/Al2O3/TiN structure RRAM devices. (March 2020) - Luo, Haipeng; Liang, Yifan; Tang, Minghua; Li, Gang; Xiong, Ying; Sun, Yunlong; Liu, Yulin; Ouyang, Sha; Xiao, Yongguang; Yan, Shaoan; Zhang, Wanli; Chen, Qilai; et al.
Abstract: Total-ionizing dose effects on the resistive switching properties of HfO2 /Al2 O3 bipolar resistive-random-access-memory devices under 60 Co γ irradiation were investigated in this study. Insignificant impact was found for 60 Co γ irradiation with a dose of 200 krad (Si) but the impact became significant for higher irradiation intensity of 1 Mrad (Si). The experiment results indicated that it is possible for device high resistance off-state or low resistance on-state to change after a total ionizing dose step stress threshold being surpassed. Moreover, it was found that the 60 Co γ irradiation of 1 Mrad (Si) caused degradation of device high-resistance state, low-resistance state, set/reset voltages, and endurance characteristics, due to the simultaneous induce of oxygen vacancies and displacement damage. Graphical abstract: Unlabelled Image